Digital health intervention in patients undergoing cardiac rehabilitation: systematic review and meta-analysis - Harbi, Ali Suleiman; Soh, Kim Lam; Yubbu, Putri; Soh, Kim Geok (F1000 Research Ltd, 2024)
Background Cardiovascular disease (CVD) continues to be the foremost mortality internationally. Cardiac rehabilitation has proven as an effective program in reducing CVD burden. Participation in cardiac rehabilitation programs is very low. Digital health intervention emerged as an alternative method to deliver Cardiac rehabilitation. This review aimed to investigate the impact of digital health intervention on the outcomes of interest Methods the following databases: PubMed, CINAHL, Scopus, and Cochrane Library have been searched to retrieve randomized controlled trials that examine the impact of digital health intervention on blood pressure, body mass index, lipid profile, blood glucose, Six-Minute Walk Test, and peak oxygen consumption. filters were set to include studies published in English between 2000-2023. Results Nineteen studies were included in this review. Six-Minute Walk Test (MD = 16.70; 95% CI: 6.00 to 27.39, p = 0.000) and maximal oxygen consumption (SMD = 0.27; 95% CI: 0.08 to 0.45, p = 0.004) significantly improved following digital health intervention, after employing the sensitivity analysis significant improvement was observed in systolic (MD = -2.54; 95% CI: -4.98 to -0.11, p = 0.04) and diastolic blood pressure (SMD = -2.0182; 95% CI: -3.9436 to -0.0928, p = 0.04) favoring experimental groups. Subgroup analysis revealed significant improvement in quality of life after three months of follow-up (SMD = 0.18; 95% CI: 0.05 to 0.31, p = 0.00), no significant differences have been observed in body mass index, lipid profile, and blood glucose. Conclusion The findings emphasize the significant impact of digital vs CBCR or usual care on physical capacity, blood pressure, and quality of life. Despite the non-statistically significant differences in body mass index and lipid profile, the comparable effect between the two methods suggests the superiority of digital over CBCR or usual care due to its convenient nature, accessibility, and cost-effectiveness.